Modulation of the Cognition-Sleep Nexus in Subjective Cognitive Decline: A 12-Week, Randomized, Double-Blind, Placebo-Controlled Trial of a Standardized Cordyceps militaris Extract - Vita Amanda; Daphne Marshall; Zahra Amir; Husin Sastranagara; Danniel Hilman Maulana; Karina Chandra; Fachrudin Sani (HM Publisher, 2025)
Subjective cognitive decline (SCD) and sleep disturbance form a vicious cycle, accelerating neurodegeneration. Cordyceps militaris (CM), a traditional medicinal fungus rich in nucleosides, possesses potent neuroprotective and adenosinergic (sleep-promoting) properties. We investigated the efficacy of a standardized CM extract on this cognition-sleep nexus in adults with SCD. This 12-week, single-center, randomized, double-blind, placebo-controlled, parallel-group trial was conducted in Palembang, Indonesia. We randomized 120 adults (aged 45-65) with SCD to receive 300 mg/day of a standardized CM mycelial extract (3% cordycepin) or a matching placebo. The primary outcome was the change from baseline in the Montreal Cognitive Assessment-Indonesian (MoCA-INA) score. Key secondary outcomes (Bonferroni-corrected) were the Pittsburgh Sleep Quality Index (PSQI), Rey Auditory Verbal Learning Test (RAVLT) Delayed Recall, and polysomnography (PSG)-derived Sleep Efficiency (SE). Analyses were performed on the Intention-to-Treat (ITT) population (N=120) using a Linear Mixed-Effects Model (LMM). The LMM analysis revealed a significant group-by-time interaction for the primary outcome, MoCA-INA (Adjusted Mean Difference [AMD]: +1.95 [95% CI: 1.10, 2.80], p < 0.001). The CM group also showed significant improvements in all three key secondary outcomes: PSQI (AMD: -2.90 [95% CI: -3.81, -1.99], p < 0.001), RAVLT Delayed Recall (AMD: +2.15 [95% CI: 1.30, 3.00], p < 0.001), and Sleep Efficiency (AMD: +5.8% [95% CI: 3.1, 8.5], p < 0.001). After FDR correction, significant benefits were also seen for processing speed, %REM sleep, and serum BDNF and hs-CRP. The intervention was well-tolerated. In conclusion, twelve weeks of supplementation with a standardized C. militaris extract significantly improved cognitive function, episodic memory, and both subjective and objective sleep in adults with SCD. These benefits were associated with enhanced neuroplasticity and reduced systemic inflammation, supporting its potential as a multi-target, disease-modifying intervention for this at-risk population.